Recent Trends In Nanoliposphere (Journal of Pharmaceutical Negative Results, 2022)
Background: Nanotechnology has generated a great deal of excitement worldwide and is being cited as the main technology ·of the 21st century. With the development of nanotechnology, the nanoliposphere has been increasingly viewed as a potential drug carrier for improving gastrointestinal absorption and oral bioavailability of some lipophilic drugs, offering multiple benefits in treating chronic human diseases by site-specific, and target-oriented delivery of specific medicines. Drug carrier systems are developed with the aim of varying the distribution of an active substance within the body and thus increasing the pharmacological efficacy and reducing its toxicity.Methods: The recent advancement of Nanotechnology offers limited toxicity and can deliver drugs with low half-life or low therapeutic index for providing sustained or controlled drug delivery action.Results: The usefulness of nanotechnology for multi-functionality of drug molecules, nanoliposphere play a promising role for attaining improved oral bioavailability of drugs for minimizing the adverse effects.Conclusion: In this context, the present review article provides details on the preparation, future development, current status, Risk, and application of nanoliposphere-based drug delivery systems for oral bioavailability of drugs. Besides, the article aims to provide readers with an expert on current developments in nanoliposphere-based nanomedicines along with prospects with them in modern drug therapy.